Human Rights Violations During Orde Baru : A Case Study Of The Distribution Ban On Bumi Manusia Books By Pramoedya Ananta Toer - I Dewa Ayu Febriani; I Made Yudana; I Wayan Kertih (CV. ULIL ALBAB CORP, 2025)
Justice is the concept that individuals must be enforced in an equal, impartial and non-arbitrary manner. Justice in providing freedom and protecting the rights of the community is the most basic pillar in the law so that Indonesia as a country of law must be able to protect these rights, namely Human Rights which include the rights to equality, protection and freedom. This research will discuss how human rights violations occurred during the Orde Baru period based on the case of the ban on the book Bumi Manusia by Pramoedya Ananta Toer. The method used is a qualitative method with a case study approach, the data collection method is carried out by the literature study method. This research is expected to be able to increase reflection on human rights. The results of this study show that there are many human rights violations obtained by Pramoedya Ananta Toer as the author of the book Bumi Manusia.